Reflections on the use of discriminatory terms based on skin color in the educational process of medical sciences) - Mercadet Portillo , Nancy Narcisa; Martínez Abreu, Judith; Estrada Rodríguez, Yonathan; Díaz Berrío , Lianelys de la Caridad (Comparative Cultural Studies: European and Latin American Perspectives, 2025)
The authors of this research work intend to reflect on the use of discriminatory terms based on skin color in the teaching-educational process in the training of future Cuban health professionals. This requires an investigation not only into the difficulties detected, but also into the causes that provoke them with a multidisciplinary approach for a subsequent design of the work strategy to follow, based on compliance with the system of actions planned for the various spaces occupied by the professional training process.